Reconstructive considerations following a necrotic spider bite on the face: A case report. (2017) - Mikkelsen, Joachim; Schmidt, Grethe; Holmgaard, Rikke
Highlights: Necrotic spider bites in the facial region can result in extensive soft tissue defects. Healing by secondary intention is slow in necrotic spider bite lesions on the face. 19-year-old female with suspected recluse spider bite on her face while sleeping. Single-stage reconstruction with a trimmed FTSG resulted in high patient satisfaction. ABSTRACT: Introduction: Spider bites as the cause of necrotic skin and soft tissue lesions occur very rarely in Central and Northern Europe. Recluse spiders, distributed almost worldwide, are one of two genera of spiders with confirmed capability of causing necrotic lesions. In the facial region, the resulting defects represent a potential reconstructive challenge, especially in younger patients. Methods: This case report has been reported in line with the SCARE criteria. Presentation of case: We describe a case of a 19-year-old female with a suspected bite from a recluse spider sustained during a recreational trip to Guatemala. She was bitten on the right upper aspect of the nose, and within a week developed a large necrotic lesion extending to the medial canthus. Following her return to Denmark the defect was reconstructed with a trimmed full-thickness skin graft. An initially planned second-stage reconstructive procedure was cancelled, as the patient was satisfied with the primary result. Discussion: Most aspects of the extended reconstructive ladder were evaluated before selecting the optimal reconstruction for this patient. In younger patients, reconstructive surgery requires special considerations, primarily due to age-related limitations combined with generally high expectations to the aesthetic outcome. Conclusion: In the few reported cases of necrotic spider bites in the facial region, active reconstructive measures have resulted in the best outcomes. Tissue expansion of local or regional skin may have a potential role, but in certain patients, simple reconstructive solutions will provide an aesthetically satisfactory result without requiring extensive or multi-stage surgeries, as demonstrated in this case.